Enhancing Pedagogy with Artificial Intelligence in Higher Secondary Schools of Doda District in Jammu and Kashmir (ShodhVarta, 2025)
In modern teaching learning process, pedagogy required an assistance of AI for effectiveness, because there is an era of technology. In present research paper the investigators tried to know about the status of awareness of Artificial Intelligence in Government Secondary School Teachers of Doda district of Jammu and Kashmir UT of India. It also tried to got the opinions of teachers towards the integration of AI in teaching learning process. The present research study is qualitative in nature. The population of the study were the Higher Secondary Schools’ teachers of Doda district of Jammu and Kashmir UT, India. As per the available data in the website of Directorate of School Education Jammu, there were total 10 Educational Zones in Doda district. The sample of the study was selected 5 teachers from each Educational Zone of Doda district (5*10=50 teachers) purposively who were aware about the usage of artificial intelligence in teaching learning process. The data was collected with the help of self-constructed interview schedule. In case of awareness about AI it is found that, teachers were aware about the AI tools such as MetaAI, ChatGPT, Google translator, Quill Bot, Google Gemini and Leonardo etc. In opinions of teachers it was found that AI helps to enlarge the learning scope, professional development, enhance the blended learning, preparing quality and attractive lesson plans. In using AI there were some cons also found such as ethical issues, plagiarism, and privacy threats etc.